Power quality analysis based on harmonic distortion level in FKEE lab, UMP - Ahmad Kamil, Fadir (2009)
Power quality is defined as any power problem manifested in voltage, current or frequency deviation that results in failure or misoperation of customer equipment. Harmonic is sinusoidal voltage or currents which has frequencies that are integer multiples of the fundamental frequency (frequency at which the supply system is designed to operate, normally 50 or 60 Hz).Firstly the harmonic current and voltage were get at substation board in FKEE lab by using power quality analyzer. After a week, the data transferred to the computer by using FLUKEVIEW software. Then, the data were compared to International Standard which is AS61000.3.6 and IEEE 519 by using Visual Basic (Microsoft Web Developer) to display it. The results show us that all the data were satisfy with the standards. During the study period (between 12 pm until 6 pm) at the lab, there were the peak period of harmonic but from 7 pm to 7 am, the harmonics were lower than before. Its shows us that the usage of the electrical equipment such as computers, lighting, motors were higher during our lab period. So, from the analysis we know when is the peak time of harmonic will occur and the sources of the harmonic. Besides that, we also know about the effect of the harmonic distortion on electrical equipment